Further validation of booklet category test subscales for learning, set loss, and memory in a mixed clinical sample. Issue 1 (2nd January 2018) - Roye, Scott; Calamia, Matthew; Greve, Kevin; Bianchini, Kevin; Aguerrevere, Luis; Curtis, Kelly
ABSTRACT: Although it has long been proposed that performance on the Booklet Category Test (BCT) relies on a number of different cognitive abilities, including executive functioning, perceptual reasoning, and memory, only a single total error score is typically derived and interpreted in clinical practice. BCT subscales based on factor analyses of subtest errors or designed specifically to measure specific cognitive domains have been proposed to better assess the multidimensional abilities underlying BCT performance. The aim of this study was to independently replicate and extend previous findings regarding the validity of these subscales. A mixed clinical sample of 137 patients completed the BCT and a number of additional measures used to assess neuropsychological domains of selective attention, various aspects of executive functioning, intellectual functioning, and memory. Correlation and regression analyses were used to explore the convergent and discriminant validity of each subscale. Subscales varied in the number and magnitude of their significant correlations with scores derived from traditional measures. In general, findings supported the convergent validity of BCT category learning, set loss, and memory subscales. However, findings regarding discriminant validity were more variable across subscales. Results provide additional support for the multidimensional nature of the BCT and the validity of derived subscales to measure specific aspects of cognitive functioning beyond what is measured by a total errors score. The recently proposed subscales examined in the current study appear to be worthy of further investigation by clinicians and researchers to determine their clinical utility.